Adoption of triply periodic minimal surface structure for effective metal hydride-based hydrogen storage. (1st January 2023) - Lesmana, Luthfan Adhy; Aziz, Muhammad
Abstract: Metal hydrides (MHs) are highly effective for storing hydrogen because of their stability, relatively low temperature and pressure, and high volumetric hydrogen density. However, their gravimetric density is low because of the weights of the MHs, leading to a low potential for mobility applications unless the reactor also acts as a body frame, thereby compensating for the light weight. Triply periodic minimal surface (TPMS) structures show great potential as heat exchangers (HEs) with extended surface properties per volume and reinforced structures designed to bear mechanical loads. Therefore, these structures are considered promising for application as hydrogen carriers, especially in MH-based hydrogen storage. This study aims to develop MH-based hydrogen storage using a TPMS structure. Furthermore, a mathematical model was developed to analyze and improve its performance in terms of the hydrogen absorption and desorption rates. The analysis using the mathematical model was validated with existing experimental data. Different cooling conditions were compared with natural convection. Moreover, finite element analysis was applied to evaluate the capability of the current structure design in withstanding the working pressure and load. This study's important finding is that the propose structure is proven to have higher hydrogen storage performance, including density and hydrogen charging and discharging performances. In addition, it is also found that improving the cooling conditions could increase the absorption rate. Forced convection (with a heat-transfer coefficient of 500 W/m 2 ·K) seems to be a preferable cooling solution that requires low energy consumption and provides sufficient cooling. By using this cooling condition with the proposed TPMS reactor design, 90% of hydrogen is absorbed within 2000 s. Natural cooling requires almost double that time. It was also found that a reactor with a TPMS structure with a 1 mm wall thickness design could withstand MH working pressure conditions and a compression load of 5000 N. Based on this finding, the TPMS-based structure can be considered as a promising novel way of storing hydrogen for mobility applications.